Uric acid levels as a predictor of cognitive function in the elderly - Yuniati, Nilasari Indah; Zerlinda, Visca; Purwanti, Sugi (Institute of Computer Science (IOCS), 2025)
This study aimed to examine the association between serum uric acid (SUA) levels and cognitive function among elderly individuals. An observational case-control study was conducted involving 37 elderly participants aged 60–75 years from As-Sakinah Elderly Integrated Health Post in Grendeng Sub-District, North Purwokerto, Indonesia. SUA levels were measured using a point-of-care testing (POCT) device, while cognitive function was assessed using the Montreal Cognitive Assessment–Indonesian version (MoCA-Ina). The mean SUA level was 5.52 ± 1.57 mg/dL, and the mean MoCA-Ina score was 19.05 ± 5.07, indicating that most participants demonstrated cognitive impairment. Pearson correlation revealed a non-significant negative association between SUA and cognitive scores (r = –0.225, p = 0.180). However, simple linear regression showed a significant inverse relationship (B = –0.214, p < 0.001), higher SUA levels were associated with lower cognitive performance. These findings suggest that while SUA may contribute to cognitive decline, it is not a standalone biomarker. Further longitudinal studies with larger samples are warranted to clarify its predictive value.